2013 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS) 2013
DOI: 10.1109/infcomw.2013.6970755
|View full text |Cite
|
Sign up to set email alerts
|

Detecting application update attack on mobile devices through network featur

Abstract: Recently, a new type of mobile malware applications with self-updating capabilities was found on the official Google Android marketplace. Malware applications of this type cannot be detected using the standard signatures approach or by applying regular static or dynamic analysis methods. In this paper we first describe and analyze this new type of mobile malware and then present a new network-based behavioral analysis for identifying such malware applications. For each application, a model representing its spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Thus, changes in permission requests might indicate behavioral changes in apps for Android platforms. Additionally, an attack on Android systems called the App Update Attack was studied by Tenenboim-Chekina et al [19].…”
Section: Android Permission and Privacy Informationmentioning
confidence: 99%
“…Thus, changes in permission requests might indicate behavioral changes in apps for Android platforms. Additionally, an attack on Android systems called the App Update Attack was studied by Tenenboim-Chekina et al [19].…”
Section: Android Permission and Privacy Informationmentioning
confidence: 99%
“…But, this technique cannot be applied in the encrypted traffic. In 2013, Tenenboim et al [25] proposed a novel network based behavioral analysis for detecting a new group of malware with self-updating capabilities which have been found in the Google Android marketplace. Their results showed that in most of the applications the threat was detected in the first five minutes after the infection occurred.…”
Section: Relate Workmentioning
confidence: 99%
“…Typical methods are being introduced through SMS phishing or social engineering techniques, intelligent detection technologies. Detecting malicious code is a difficult task because there are new malicious codes emerges as improvement in detecting technology [5,11]. (Table 1).…”
Section: Types Of Personal Information Disclosure On the Android Platmentioning
confidence: 99%